History of the Arabs : From the Earlist Times to the Present - Hitti, Philip K. (UK Palgrave Macmillan, 2002)
This ... study of the Arabians and the Arabic-speaking peoples is a ... source of information on Arab history. Suitable for both scholars and the general reader, it unrolls one of the richest and most instructive panoramas in history, telling with insight the story of the rise of Islam in the Middle Ages, its conquests, its empire, its time of greatness and of decay. For this revised tenth edition, Walid Khalidi's timely preface emphasises that now, more than ever, this magisterial work is of vital importance to the on-going attempts to bridge the Arab/Western cultural divide.-Publisher description.
Include Index and Maps
Keywords: Arabs -- Civilization, Arab -- Arabian Peninsula -- Islamic Empire